Multifaceted roles of mitochondria in wound healing and chronic wound pathogenesis - Hunt, Matthew; Torres, Monica; Bachar-Wikström, Etty; Wikström, Jakob D. (Frontiers in Cell and Developmental Biology, 2023)
Mitochondria are intracellular organelles that play a critical role in numerous cellular processes including the regulation of metabolism, cellular stress response, and cell fate. Mitochondria themselves are subject to well-orchestrated regulation in order to maintain organelle and cellular homeostasis. Wound healing is a multifactorial process that involves the stringent regulation of several cell types and cellular processes. In the event of dysregulated wound healing, hard-to-heal chronic wounds form and can place a significant burden on healthcare systems. Importantly, treatment options remain limited owing to the multifactorial nature of chronic wound pathogenesis. One area that has received more attention in recent years is the role of mitochondria in wound healing. With regards to this, current literature has demonstrated an important role for mitochondria in several areas of wound healing and chronic wound pathogenesis including metabolism, apoptosis, and redox signalling. Additionally, the influence of mitochondrial dynamics and mitophagy has also been investigated. However, few studies have utilised patient tissue when studying mitochondria in wound healing, instead using various animal models. In this review we dissect the current knowledge of the role of mitochondria in wound healing and discuss how future research can potentially aid in the progression of wound healing research.